Variation in Mortality and Ageing Rate in a Fast‐Paced Species: Insights From 24 Years of Hazel Dormouse (Muscardinus avellanarius) Data - Thomas Bjørneboe Berg; Fernando Colchero; Owen R. Jones; Lene Sanderhoff; Rimvydas Juškaitis (Ecology and Evolution, 2025)
ABSTRACT Recent research has found that, among some mammal species, differences in environmental conditions among populations of the same species drive changes in infant and juvenile mortality, but not in the rate of senescence, also known as the rate of ageing. Although this pattern has been confirmed in primates and some carnivores, it remains untested on other taxonomic groups with faster life histories, such as rodents. Here, we analysed age‐specific survival in Hazel Dormouse, using a 24‐year capture‐mark‐recapture data set from Lithuania. We used Bayesian survival trajectory analysis (BaSTA) and tested different models of age‐specific mortality. The population has experienced three distinct demographic phases—increasing (1999–2006), declining (2007–2014) and stable‐low abundance (2015–2022). We divided the dataset into these three periods to assess changes in survival over time. During all three periods, the life expectancy of males was larger than that of females, contrary to the general mammalian trend of higher female survival. Differences in survival among the three periods were primarily due to changes in age‐independent mortality and ageing rates, but not due to changes in juvenile mortality. Our findings support the notion that the low variance rate of ageing is limited to species with slow life histories. However, they also suggest that rodents, even those like the Hazel Dormouse which can reduce exposure to external threats, can substantially modulate their ageing rates in response to environmental variation.